Biomass accumulation and productivity of sunflower grown under organic and mineral fertilization (Research, Society and Development, 2021)
The accumulation of dry matter in the sunflower is extremely important for grain production, in which, when it has inadequate fertilization, production is impaired. The objective was to evaluate the biomass accumulation and grain yield of sunflower fertilized with NPK formulations (mineral and organomineral). The experiment was carried out in a greenhouse, located in an experimental area of ​​IFGoiano - Campus Rio Verde - GO, in the municipality of Rio Verde, Goiás. The experimental design used was in randomized blocks, analyzed in a 4 × 2 factorial scheme with three repetitions. The treatments consisted of four doses of the formulated 04-14-08 NPK: 50, 100, 150 and 200% of the corresponding recommendation, 90 kg ha-1 of N, 180 kg ha-1 of P and 40 kg ha-1 of K for sunflower culture and two mineral and organomineral sources. The application of formulations in the respective sources and dosages was carried out at sowing. Analyzes of dry matter accumulation, water mass and grain yield were performed. The mineral NPK source provides greater fresh mass of the leaves, dry mass of the stem, water mass and dry mass of the aerial part of the sunflower than the orgnomineral source. The doses of 162 and 138% of the NPK recommendation, via mineral and organomineral source, provide the highest grain yield for sunflower cultivation, respectively.